Association of Oxytocin and Parental Prefrontal Activation during Reunion with Infant: A Functional Near-Infrared Spectroscopy Study - Ito, Jun; Fujiwara, Takeo; Monden, Yukifumi; Yamagata, Takanori; Ohira, Hideki (Frontiers in Pediatrics, 2017)
Although previous studies have revealed the role of oxytocin (OT) in parental behavior, the role of OT has not been investigated through the direct assessment of prefrontal brain activation during parenting. By using functional near-infrared spectroscopy, we aimed to show the relationship between parental [maternal (N = 15) and paternal (N = 21)] OT levels and the activation of the prefrontal cortex (PFC), while holding their infants after separation. Baseline OT levels were measured in the subjects’ saliva samples before the experiment. Prefrontal brain activation was assessed in participants sitting alone on a chair (i.e., separation from their infant for 120 s) and during the target period (i.e., holding their infant for 45 s), which was done in triplicate. The oxygen hemoglobin (oxy-Hb) dissociation curve significantly increased in 9 out of 22 channels on the PFC when maternal and paternal samples were combined. However, only the fathers showed a correlation between salivary OT and oxy-Hb signal. Furthermore, while holding their infants, high-OT fathers showed left hemispheric dominance compared to low-OT fathers, while high-OT mothers showed right hemispheric dominance compared to low-OT mothers. This study showed that fathers with high-OT levels showed neural activation with left hemispheric dominance, while holding their infants, suggesting that increase of OT level might activate paternal PFC related to parenting behavior, although the same is not true for mothers.